2013
DOI: 10.1016/j.jcrs.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visual quality with satisfaction and function in a normal cohort of pseudophakic patients

Abstract: When evaluating a highly controlled population with expected high satisfaction after cataract surgery, pseudophakic dysphotopsia was clearly the only significant dissatisfier. Furthermore, dysphotopsia highly correlated with the NEI VF-11R questionnaire; thus, symptoms of dysphotopsia are also seen to have functional significance. A shortened NEI VFQ survey and satisfaction correlated strongly with the full survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…We think this might be related to patient selection. van Bree et al, 11 Lapid-Gortzak et al, 21 and Kinard et al 27 enrolled only subjects with a high-quality state of their eyes. The 2 other studies reported relatively high average straylight values, of which Guo et al 34 showed the highest.…”
Section: Discussionmentioning
confidence: 99%
“…We think this might be related to patient selection. van Bree et al, 11 Lapid-Gortzak et al, 21 and Kinard et al 27 enrolled only subjects with a high-quality state of their eyes. The 2 other studies reported relatively high average straylight values, of which Guo et al 34 showed the highest.…”
Section: Discussionmentioning
confidence: 99%
“…5 Briefly, a retrospective review of Moran Eye Center, University of Utah, Salt Lake City, Utah, USA, surgery logs was used to determine patients' eligibility for clinical study evaluation. Participation in the study involved a single visit to the Moran Eye Center outpatient clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included central corneal pathology other than mild guttata, glaucoma, macular pathology except for minimal hard drusen without changes to the retinal pigment epithelium, diabetic retinopathy other than minimal nonproliferative background diabetic retinopathy, any cause of central visual acuity loss including optic nerve or occipital cortex dysfunction, amblyopia, dry-eye syndrome, central posterior capsule opacification, and any contraindication to pupil dilation. To increase the study sample size, the study included patients 45 years or older (rather than 50 years, which was the lower age limit of the cohort in the Kinard et al study 5 ). All eligible patients who consented to participate had an ophthalmic examination that included slitlamp biomicroscopy and imaging, with and without retroillumination, to confirm the presence of glistenings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Today cataract surgery aims to deliver 6/6 snellen's visual acuity (VA) to the patient and patient expectations are also on the rise. Dysphotopsia, virtually unknown two decades ago 6 , has become the leading problem following uneventful, cataract surgery with clear cornea and in the bag IOL. Once the patient's thought process becomes fixated on it, it doesn't disappear easily.…”
Section: Introductionmentioning
confidence: 99%